Mathematical analysis and homogenization of the torsion problem - Dag Lukkassen; Annette Meidell; Peter Wall (Journal of Function Spaces and Applications)
In this paper we address the limitations of the classical formulation of the torsion problem and give a self-contained survey of the function spaces and formulations that are more suitable for analysing the torsional behavior of composite materials. We also prove some homogenization results for the torsion problem in both the periodic and stochastic setting. Our theoretical results are illustrated by numerical examples.